2009
DOI: 10.1002/pits.20423
|View full text |Cite
|
Sign up to set email alerts
|

Training school psychologists in psychopharmacology consultation

Abstract: The number of children taking psychotropic medications has dramatically increased in recent years. These children typically take medication during school hours, thereby making the school setting an optimal venue in which evaluate the effectiveness of medications. Given their training in data‐based decision making, intervention, and assessment, school psychologists should be involved in the evaluation of medication effectiveness in children at school. However, many school psychology programs do not offer formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Whereas students in nondoctoral programs may receive basic training in SMHS, they may also need to pursue postgraduate training in SMHS because nondoctoral programs are shorter in length than doctoral‐level programs. Our rationale for the courses listed in Table 1 is based on what has been presented in the school psychology literature as being a necessary part of the SMHS expanded role of school psychologists (Roberts, Floress, & Ellis, 2009; Semrud‐Clikeman, 2005; Tharinger & Palomares, 2004). Integrated within the subsections below is a discussion of ethical and professional practice issues related to the provision of SMHS.…”
Section: Preparation and Training Of School Psychologistsmentioning
confidence: 99%
“…Whereas students in nondoctoral programs may receive basic training in SMHS, they may also need to pursue postgraduate training in SMHS because nondoctoral programs are shorter in length than doctoral‐level programs. Our rationale for the courses listed in Table 1 is based on what has been presented in the school psychology literature as being a necessary part of the SMHS expanded role of school psychologists (Roberts, Floress, & Ellis, 2009; Semrud‐Clikeman, 2005; Tharinger & Palomares, 2004). Integrated within the subsections below is a discussion of ethical and professional practice issues related to the provision of SMHS.…”
Section: Preparation and Training Of School Psychologistsmentioning
confidence: 99%
“…For review of this subject matter see the article by Ball, Kratochwill, Johnston, and Fruehling (2009). Although a relatively small number of professionals hold such privileges, as discussed by Roberts, Floress, and Ellis (2009) in their article, pharmacological consultation may be the arena in which the greatest impact of the role of psychological professionals may be seen. Truly, although medical professionals ranging from primary care physicians to neurologists and psychiatrists prescribe the various medications discussed in the preceding articles, they are not usually afforded the time that psychological professionals are to engage in more in-depth observations and assessment, both in and outside of the school.…”
Section: Roles Of Psychological Professionals In Pharmacological Intementioning
confidence: 96%
“…In turn, both the clinical practice of the medical professionals and the practice of the psychological professionals benefit from this consultative relationship, which will likely equate to increased positive outcomes for the child or adolescent. For more thorough coverage of issues pertaining to psychopharmacological consultation, see Roberts et al (2009).…”
Section: Roles Of Psychological Professionals In Pharmacological Intementioning
confidence: 99%
“…Using this evaluation model, school psychologists can offer empirical support to prescribing physicians to inform treatment decision-making. School psychologists' training in data-based decision-making, intervention, and program evaluation makes this a logical practice role (Roberts et al 2009). …”
Section: What Roles Can School Psychologists Undertake?mentioning
confidence: 98%
“…School psychologists appear to be well positioned to provide these additional therapeutic supports in the form of cognitive-behavioral therapy, behavioral management instruction, family support groups, and social skills training. Roberts et al (2009) highlighted the consultative roles in which trained school psychologists may perform. These authors specifically demonstrated how behavioral consultation models (e.g., Kratochwill and Bergan 1990) can be used to evaluate the effect of psychotropic medication within a problem-solving approach.…”
Section: What Roles Can School Psychologists Undertake?mentioning
confidence: 99%